Dimensions and Mechanisms of Environmental Behavior Among Visitors to Nature-Based Destinations: A Case Study of Gunung Ciremai National Park, Indonesia - Asih, Sekar Sari Melati; Nugroho, Prasetyo (Jurnal Sylva Lestari, 2025)
Nature-based tourism in national parks (NP) plays a significant role in promoting environmentally responsible behavior (EB) among individuals. While studies on visitors’ EB are increasing, research focusing specifically on visitors’ EB in NPs within developing countries, such as Indonesia, remains limited. This study aims to identify factors shaping visitors’ EB through an extended Theory of Planned Behavior (TPB) at Gunung Ciremai National Park (GCNP). To explore the dimensions and mechanisms of EB—categorized as environmentally conservative behavior (ECB), environmentally disturbing behavior (EDB), and environmentally radical behavior (ERB)—an extended TPB framework was utilized. TPB examines the relationships among the following latent variables: attitude toward behavior (ATB), subjective norm (SN), perceived behavioral control (PBC), environmental behavior intention (EBI), and environmental behavior (EB). Data were collected from 452 completed questionnaires at three nature-based destinations in GCNP. The study demonstrates clear evidence that the hypothesized relationships among ATB, SN, PBC, EBI, and EB were valid across different types of environmental behavior. The results highlight that these determinant factors work together in shaping visitors’ environmental behavior based on TPB. However, their influence may differ depending on the specific type of behavior being considered. The study underscores the need for NPs managers to go beyond simply raising visitors’ awareness of the importance of environmental conservation. Efforts should also focus on enhancing visitors’ self-efficacy in performing environmentally responsible behaviors. Keywords: forest-based ecosystem services, national park, nature-based tourism, Theory of Planned Behavior